Consultations in Results-Focused Capacity Development : Reviews of Project Experiences in East Africa Using the Capacity Development and Results Framework - World Bank (Washington, DC, 2015)
Capacity is often seen to be the principal constraint to development, and each year aid donors spend more than $30 billion globally to address this issue. However, most capacity development efforts fail to yield satisfactory results. Important deficiencies include low stakeholder commitment to development goals; weak understanding of institutional capacities and how they need to change to support these goals; lack of strategy around what results to support and how; poor planning of activities to support local agents in driving change; inadequate attention to needed adjustments of change processes; and not learning from previous successes and mistakes. These deficiencies necessitate fundamental changes in how capacity development is defined and practiced. Capacity development means enhancing the ability of local leaders, groups and coalitions to effect institutional change. It entails understanding both the demand and supply sides of the development process. WBI worked with local partners to review and document the projects. Through the participatory reviews, WBI learned how to better work with local partners in supporting efforts to apply results-focused approaches. The local partners learned how the application of results-focused tools, locally adapted to their context, could help a project achieve the most needed results. Development practitioners and local partners can apply the lessons learned from these reviews to help improve the design and implementation of their own capacity development programs.